Bioinspired Structural Composite Hydrogels with a Combination of High Strength, Stiffness, and Toughness. (28th April 2021) - Ji, Donghwan; Nguyen, Thanh Loc; Kim, Jaeyun
Abstract: In the development of artificial hydrogels, emulating the mechanical properties of biological tissues with a desirable combination of stiffness and toughness is crucial. To achieve such properties, a design principle inspired by a natural structural composite to wet hydrogels is applied. The bioinspired structural composite hydrogel consisting of layered microplatelets and polymer matrix with strong polymer–platelet interactions is fabricated by a facile method, that is, drying‐induced unidirectional shrinkage and rehydration process coupled with secondary ionic crosslinking. The resulting hydrogels exhibit a combination of high tensile strength and elastic modulus (on the order of several MPa) and high fracture energy (up to ≈ 2 kJ·m −2 ). The results suggest the potential of the bioinspired approach that is limitedly applied in dry composites for developing mechanically robust composite hydrogels. Abstract : Hydrogels achieve a unique combination of mechanical properties by applying the design principle of a natural structural composite. The integration of layered microplatelets and densified polymer matrix with improved polymer–platelet interactions are implemented by a facile method, resulting in the combination of high tensile strength, elastic modulus, and fracture energy.